2005
DOI: 10.1634/stemcells.2004-0197
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin‐3 Expression in Human Fetal Airway Epithelial Progenitor Cells

Abstract: Airway epithelium stem cells have not yet been prospectively identified, but it is generally assumed that both secretory and basal cells have the capacity to divide and differentiate. Previously, we developed a test for progenitor cells of the human airway epithelium, relying on the transplantation of fetal respiratory tissues into immunodeficient mice. In this study, we hypothesized that airway-repopulating epithelial progenitors can be marked with surface antigens, and we screened an array of such candidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…Some suggest that both populations can restore the tracheal epithelium equally well (Avril-Delplanque et al, 2005;Liu et al, 1994). However, others have found that only columnar cells (Johnson and Hubbs, 1990) or only basal cells (Ford and Terzaghi-Howe, 1992) can restore all of the epithelial cell types.…”
Section: Box 2 Transdifferentiationmentioning
confidence: 99%
“…Some suggest that both populations can restore the tracheal epithelium equally well (Avril-Delplanque et al, 2005;Liu et al, 1994). However, others have found that only columnar cells (Johnson and Hubbs, 1990) or only basal cells (Ford and Terzaghi-Howe, 1992) can restore all of the epithelial cell types.…”
Section: Box 2 Transdifferentiationmentioning
confidence: 99%
“…In vivo and in vitro studies show that epithelial repair is rapid and dynamic, involving epithelial dedifferentiation, cytoskeletal rearrangement, migration, and redifferentiation (e.g., see References 54-56). Indeed, both basal and columnar cell types reconstituted a complete epithelium in an in vivo model of rat tracheas denuded of their own cells and implanted in immune compatible hosts (57,58). However, colony formation on plastic dishes (59) and lineage tracing studies (60), as well as more recent analysis of clonal growth (61) and genetic lineage mapping (62,63), suggest that mouse tracheal basal cells have enhanced ability to form large differentiated epithelial colonies.…”
Section: Adult Lung Epithelial Stem Cellsmentioning
confidence: 99%
“…Consequently, viable respiratory BCs cannot be isolated on the basis of K expression. To overcome this issue, several groups identified cell-surface markers that can be used to separate BCs into subsets, using a fluorescence-activated cell sorter (FACS) (2,3,(8)(9)(10). One of these markers, tissue factor (TF), is a component of the extrinsic coagulation cascade (11), and was originally developed for the isolation of nasal polyp BCs (12).…”
mentioning
confidence: 99%